Collier's conflict of laws - Rogerson, Pippa (Cambridge : Cambridge University Press, 2016)
"This reworked version of Conflict of Laws introduces a new generation of students to the classic. It has been completely rewritten to reflect all the recent developments including the increased legislation and case law in the field. The author's teaching experience is reflected in her ability to provide students with a clear statement of rules which sets out a framework to the subject, before adding detail and critical analysis. Recognising that the procedural aspect of the subject challenges most students, the book explores conflict of laws in its practical context to ensure understanding. Teachers will appreciate the logical structure, which has been reworked to reflect teaching in the field today. Retaining the authority that was the hallmark of the previous edition, this contemporary and comprehensive textbook is essential reading"--
9 CHOICE OF LAW RULES, p.264 -- 1. Introduction, p.264 -- 2. Analysis, p.264 -- 3. Connecting factors, p.266 -- 4. Characterisation, p.267 -- 5. The incidental question, p.277 -- 6. Renvoi, p.280 -- 7. Time factor, p.288 -- 10 CONTRACTUAL OBLIGATIONS, p.291 -- 1. Introduction, p.291 -- 2. Background to Rome I Regulation, p.294 -- 3. Temporal scope and interpretation, p.294 -- 4. Material scope and exceptions, p.295 -- 5. Effect of applicable law, p.297 -- 6. General rules, p.300 -- 7. Special rules, p.317 -- 8. Formal validity, p.319 -- 9. Capacity, p.320 -- 10. Exceptions to the applicable law, p.321-- 11. Public policy and mandatory rules, p.323 -- 12. Effect of illegality on a contract, p.329 -- 13. Unilateral rules, p.333 -- 14. Liability in both contract and tort, p.333 -- 11 NON-CONTRACTUAL OBLIGATIONS, p.335 -- 1. Introduction, p.335 -- 2. Universal application and interpretation, p.337 -- 3. Temporal scope, p.338 -- 4. 'Non-contractual obligation', p.339 -- 5. Exdusion of renvoi, p.342 -- 6. Habitual residence, p.342 -- 7. Damage, p.343 -- 8. Effect of the applicable law, p.343 -- 9. Applicable law of non-contractual obligations arising out of a tort/delict, p.346 -- 10. Rules of safety and conduct, p.355 -- 11. Particular non-contractual obligations, p.355 -- 12. Parties' choice of law, p.362 -- 13. Liability in both contract and tort, p.363 -- 14. Effect of a contract limiting liability, p.364 -- 15. Mandatory rules and public policy, p.365 -- 16. Defamation, ete. (the common law rule of double actionability), p.366 -- 17. Trusts, p.369 -- 12 PROPERTY p.377 -- 1. Introduction, p.377 -- 2. Characterisation, p.377 -- 3. Immovables, p.380 -- 4. Tangible movables, p.385 -- 5. Intangible property, p.396 -- 6. Involuntary transfers, p.405 -- 13 AVOIDING THE RESULTS OF THE CHOICE OF LAW PROCESS, p.412 -- 1. Introduction, p.412 -- 2. Substance and procedure, p.412 -- 3. Renvoi, p.423 -- 4. Public policy, p.424 -- 5. Unilateral choice of law rules, p.433 -- 6. Mandatory rules, p.434.
Includes bibliographical references and index.
Keywords: Conflict of laws; Conflict of laws -- England